Dietary analysis of the Barn Owl (Tyto alba) in the Souk-Ahras region (Khemissa). - DJELLABI Soundes (My University, 2026)
The Barn Owl (Tyto alba) is a cosmopolitan nocturnal raptor occupying the apex of open-habitat food webs worldwide. This work presents the first dietary study of this species in the Souk Ahras region (northeastern Algeria), based on the analysis of 277 rejection pellets collected from September 2025 to March 2026 at a roost site within the classified Roman archaeological monument of Khemissa. Pellet dissection yielded 593 prey items across seven taxa: mammals (Mus musculus, Crocidura sp., Rattus rattus), Coleoptera, birds, and amphibians. The house mouse Mus musculus overwhelmingly dominated the diet (NF = 87.86%, OF = 98%, BF = 94.01%), reflecting the high density of this commensal rodent in the region's cerealfarming landscapes. Monthly diversity indices (H' = 0.45–0.60; J = 0.33–0.55; BP = 0.82–0.89) confirmed persistently low trophic diversity. Seasonal analysis showed no significant change in prey composition between autumn and winter (χ² = 4.939; p = 0.552); only Pielou's evenness increased slightly in winter (p = 0.0497) due to the seasonal disappearance of Coleoptera. Multivariate analyses (PCA and CA) confirmed a moderate seasonal gradient. Total estimated biomass consumed reached 9,975 g, 94% attributable to Mus musculus. This study provides the first quantitative assessment of the natural biocontrol service delivered by Barn Owls in the agricultural landscapes of Souk Ahras. ---------------------------------------------------------------------------------------------------------------------------------------------------------------- بومة الحظيرة ) (Tyto albaجارحة ليلية منتشرة في جميع انحاء العالم تحتل قمة السلاسل الغذائية في البيئات المفتوحة. يمثل هذا العمل اول دراسة للنظام الغذائي لهذا النوع في ولاية سوق اهراس) شمال شرق الجزائر( ، استنادا الى تحليل 277كرة نبذ جمعت من سبتمبر 2025الى مارس 2026في موقع مبيت داخل الأثر الروماني المصنف خميسة. كشف تشريح الكرات عن 593فريسة تنتمي الى سبعة أصناف: ثدييات ) ،(Mus musculus; Crocidura sp.; Rattus rattusخنافس، طيور وبرمائيات. هيمن الفار المنزلي Mus musculusهيمنة سبه مطلقة على النظام الغذائي )% ،(NF = 87.86%; OF = 98%; BF = 94.01وهو ما يعكس كثافته العالية في الأنظمة الزراعية الحيوية بالمنطقة. اكدت مؤشرات التنوع الشهرية ) (H’ = 0.45-0.60; J = 0.33-0.55; BP = 0.82-0.89انخفاضا مستمرا في التنوع الغذائي. اظهر التحليل الموسمي استقرارا في تركيب الفرائس بين الخريف والشتاء ) ،( χ² = 4.939 ; p = 0.552ولم يرتفع سوى معامل تساوي بيلو طفيفا في الشتاء ) (p = 0.0497بسبب اختفاء الخنافس الموسمي. اكدت التحليلات متعددة المتغيرات) AFCو (ACPوجود تدرج موسمي معتدل. قدرت الكتلة الحيوية الاجمالية للفرائس المستهلكة ب 9975غ، يعود %94منها الى . Mus musculusتقدم هذه الدراسة لأول مرة تقييما كميا لخدمة المكافحة الحيوية الطبيعية التي تؤديها بومة الحظيرة في الأراضي الزراعية في سوق اهراس ------------------------------------------------------------------------------------------------------------------------------------------------------------------ La Chouette effraie (Tyto alba) est un rapace nocturne cosmopolite occupant le sommet des chaînes alimentaires des milieux ouverts. Ce travail constitue la première étude du régime alimentaire de cette espèce dans la wilaya de Souk Ahras (nord-est algérien), à partir de l'analyse de 277 pelotes de réjection collectées de septembre 2025 à mars 2026 sur un site de gîte situé au sein du monument archéologique romain de Khemissa. La dissection des pelotes a livré 593 proies appartenant à sept taxons : mammifères (Mus musculus, Crocidura sp., Rattus rattus), coléoptères, oiseaux et amphibiens. La souris domestique Mus musculus domine massivement le spectre alimentaire (NF = 87,86 %, OF = 98 %, BF = 94,01 %), révélant un régime hyper-spécialisé lié à l'abondance de ce rongeur dans les agrosystèmes céréaliers de la région. Les indices de diversité mensuels (H' = 0,45–0,60 ; J = 0,33–0,55 ; BP = 0,82–0,89) confirment une faible diversité trophique. L'analyse saisonnière montre une stabilité statistique du régime entre l'automne et l'hiver (χ² = 4,939 ; p = 0,552) ; seule l'équitabilité de Pielou augmente légèrement en hiver (p = 0,0497), en raison de la disparition saisonnière des coléoptères. Les analyses multivariées (ACP et AFC) confirment un gradient saisonnier modéré. La biomasse totale consommée est estimée à 9 975 g, dont 94 % imputable à Mus musculus. Cette étude établit pour la première fois un bilan quantitatif du service de biocontrôle naturel assuré par la Chouette effraie dans les terres agricoles de Souk Ahras.
Keywords: Tyto alba; Souk Ahras; dietary analysis; Mus musculus; rejection pellets; trophic diversity; biocontrol; ،Tyto albaسوق اهراس، النظام الغذائي، ،Mus musculusكرات النبذ، التنوع الغذائي، المكافحة الحيوية; régime alimentaire; pelotes de réjection; diversité trophique; biocontrôle